(untitled) (American Journal of Medical Science and Innovation, 2025)
Luangprabang City is currently confronting a substantial wastewater management crisis, primar-ily due to the lack of an operational domestic sewage system and insufficient wastewater treatment technology. This study aimed to assess the current state of domestic wastewater management and investigate wastewater treatment technologies within a circular economic framework that is suitable for local conditions. Data were collected from local institutions encompassing local policies, legis-lation, wastewater treatment facilities, site visits, and observations. Secondary data were sourced from the literature reviews, technical guidelines, and related articles. Three distinct wastewater treatment technologies were evaluated to ascertain the optimal feasibility of the interventions for comparison purposes. The technical and treatment efficiencies of these technologies were also ana-lyzed. The financial aspects were assessed, with an assumed affordability rate of 3%, a discount rate of 4.5%, and a project period of 10 years. The indicators employed included net present value and benefit-cost ratio. Based on the results of the analysis, the DEWATS Module with a constructed wetland was the most suitable option for implementation in the study area.